2010
DOI: 10.3109/02688690903374059
|View full text |Cite
|
Sign up to set email alerts
|

Does drill-induced noise have an impact on sensorineural hearing during craniotomy procedure?

Abstract: We conclude that drill-generated noise during craniotomy has been incriminated as a cause of SNHL. Possible noise disturbance to the inner ear can only be avoided by minimizing the number of burr holes and the duration of harmful noise exposure to the cochlear structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…6 Farzanegan et al showed that patients undergoing supratentorial craniotomy for brain tumor resection developed SNHL that was restricted to the higher frequencies. 8 Despite taking precautions to reduce operative trauma to the vestibulocochlear nerve, using a retractorless technique, a small number of patients in this study did have HFHL following MVD. While some of the HFHL observed may be due to operative manipulation that can never be truly avoided, drill-induced acoustic damage remains a possible etiology in these patients.…”
Section: Drill-induced Snhlmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Farzanegan et al showed that patients undergoing supratentorial craniotomy for brain tumor resection developed SNHL that was restricted to the higher frequencies. 8 Despite taking precautions to reduce operative trauma to the vestibulocochlear nerve, using a retractorless technique, a small number of patients in this study did have HFHL following MVD. While some of the HFHL observed may be due to operative manipulation that can never be truly avoided, drill-induced acoustic damage remains a possible etiology in these patients.…”
Section: Drill-induced Snhlmentioning
confidence: 99%
“…8,28 Drill-generated noise may damage hearing by either mechanical stretch of the inner-ear structures or through metabolic changes in the cochlear cells. 6 Farzanegan et al showed that patients undergoing supratentorial craniotomy for brain tumor resection developed SNHL that was restricted to the higher frequencies.…”
Section: Drill-induced Snhlmentioning
confidence: 99%
“…3 When a drill is used during a mastoid surgery, the noise level in the cochlea is calculated from vibration measurements on intact skulls of human cadavers and temporal bones. 4 Everytime when a drill is used, the ipsilateral cochlea is exposed to noise levels of about 100 dB and the contralateral cochlea to levels of 5 to 10 dB lower. 5 For example, when drilling in the mastoid cavity, the noise levels range from 85 to 117 dB.…”
Section: Introductionmentioning
confidence: 99%
“…9,20 Similar results were also reported in asso- ciation with elective craniotomy when audiograms were performed before and after the procedure. 7 These studies found that drill-generated noise during craniotomy significantly affected high-frequency (4-6 kHz) but not lowfrequency (0.25-2 kHz) hearing. As noted, the short outer hair cells of the high-frequency region have been found to be more vulnerable to sound stimulation than the taller receptor cells in the low-frequency area.…”
Section: Discussionmentioning
confidence: 99%